Entry of Escherichia coli into stationary phase is indicated by endogenous and exogenous accumulation of nucleobases. - Rinas, U (1995)
Endogenous and exogenous accumulation of nucleobases was observed when Escherichia coli entered the stationary phase. The onset of the stationary phase was accompanied by excretion of uracil and xanthine. Except for uracil and xanthine, other nucleobases (except for minor amounts of hypoxanthine), nucleosides, and nucleotides (except for cyclic AMP) were not detected in significant amounts in the culture medium. In addition to exogenous accumulation of nucleobases, stationary-phase cells increased the endogenous concentrations of free nucleobases. In contrast to extracellular nucleobases, hypoxanthine was the dominating intracellular nucleobase and xanthine was present only in minor concentrations inside the cells. Excretion of nucleobases was always connected to declining growth rates. It was observed in response to entry into the stationary phase independent of the initial cause of the cessation of cell growth (e.g., starvation for essential nutrients). In addition, transient accumulation of exogenous nucleobases was observed during perturbations of balanced growth conditions such as energy source downshifts. The nucleobases uracil and xanthine are the final breakdown products of pyrimidine (uracil and cytosine) and purine (adenine and guanine) bases, respectively. Hypoxanthine is the primary degradation product of adenine, which is further oxidized to xanthine. The endogenous and exogenous accumulation of these nucleobases in response to entry into the stationary phase is attributed to degradation of rRNA.